Urea water bath: A novel treatment for monogenean parasite infections in hagfish (Agnatha: Myxiniformes: Myxinidae) - Taketeru Tomita; Hiroko Takaoka; Nozomi Hanahara (MethodsX, 2025)
Monogenean flatworms are pathogenic parasites that infect the skin of marine fish and pose a major problem in aquaculture and aquarium industries. Freshwater baths are the most commonly used method to treat these infections. However, this method is not suitable for certain fish taxa, including hagfish (Agnatha: Myxiniformes: Myxinidae), which have low tolerance to hypoosmotic environments.In the present study, we developed a treatment fluid specifically for use in hagfish. The fluid was prepared by dissolving urea in a mixture of chlorine-free tap water and seawater. A 5-min bath of three captive purple hagfish in the fluid successfully eliminated the parasites, with no apparent side effects. To date, this is the only known effective treatment for monogenean infections in hagfish. • In this study, we developed a method to treat monogenean infections in hagfish. • This method uses a fluid containing a high concentration of urea. • Bathing infected hagfish in the fluid successfully eliminated the parasites without apparent side effects.